2021
DOI: 10.1007/s11606-021-06953-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Curfew Effective in Limiting SARS-CoV-2 Progression? An Evaluation in France Based on Epidemiokinetic Analyses

Abstract: Background Since late summer 2020, the French authorities implemented a curfew/lightened lockdown-alternating strategy instead of strict lockdown, to improve acceptability and limit socioeconomic consequences. However, data on curfew-related efficacy to control the epidemic are scarce. Objective To investigate the effects on COVID-19 spread in France of curfew combined to local and/or nationwide restrictions from late summer 2020 to mid-February 2021. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Indeed, although the effectiveness of lockdowns in containing the spread of COVID-19 is still controversial (Dainton & Hay, 2021), this chapter follows the empirical findings of Mégarbane et al (2021) and Alfano and Ercolano (2020), which positively correlate restrictive social mobility policies with rule compliance and public safety.…”
mentioning
confidence: 76%
“…Indeed, although the effectiveness of lockdowns in containing the spread of COVID-19 is still controversial (Dainton & Hay, 2021), this chapter follows the empirical findings of Mégarbane et al (2021) and Alfano and Ercolano (2020), which positively correlate restrictive social mobility policies with rule compliance and public safety.…”
mentioning
confidence: 76%
“…This finding underscores the influence of curfews on transportation patterns and highlights their effectiveness in controlling mobility. Some studies have found that imposing curfew was effective in altering the spread of COVID-19 epidemic ( 33 35 ). This study also reveals the significant impact of public transportation on the movement of people within the country.…”
Section: Discussionmentioning
confidence: 99%